Analysis of glucose metabolism outcomes 4–7 years postpartum in women with gestational diabetes mellitus using continuous glucose monitoring maternal risk factors: a Chinese cohort study - Zhao, Dan; Yuan, Ning; Zhao, Xin; Sun, Jianbin; Xu, Xiumei; Zhang, Xiaomei (Frontiers in Endocrinology, 2025)
BackgroundThis study investigates glucose metabolism outcomes and glycemic variability in women with gestational diabetes mellitus (GDM) 4–7 years postpartum. It also identifies maternal risk factors for glucose metabolism abnormalities (GMA) to support early prevention strategies.MethodsA bidirectional cohort study was conducted with 60 women with GDM and 60 without GDM, recruited from Peking University International Hospital between 2017 and 2019. Participants underwent oral glucose tolerance tests at 4–7 years postpartum and were categorized into GMA and normal glucose tolerance groups. Continuous glucose monitoring assessed glycemic variability, and logistic regression identified early pregnancy risk factors for postpartum GMA.Results(1) Women with a history of GDM have a higher incidence of GMA 4–7 years postpartum (p< 0.001). (2) They also showed increased cardiovascular risk factors 4–7 years postpartum, including diastolic blood pressure, body fat ratio, and interleukin-6 (p<0.05). (3) Blood glucose variability is significantly higher in all participants with a history of GDM, even in the normal glucose tolerance group. (4) Independent early pregnancy predictors of postpartum GMA included pre-pregnancy body mass index (BMI), the triglyceride-glucose index, and a history of GDM (AUC = 0.870, 95% CI: 0.808–0.931).ConclusionsWomen with a history of GDM are at a higher risk of GMA and glycemic variability 4–7 years postpartum. Pre-pregnancy BMI, the triglyceride-glucose index, and GDM history are strong predictors of postpartum GMA, highlighting the need for early intervention.Clinical trial registration: China Clinical Trials Registry, identifier ChiCTR2300067592.